Voorwoord (The broad connection) (Bulletin KNOB, 1992)
On October the 11th 1991 the symposium The broad connection took place in the church of the Evangelic Community of Brethren at Zeist. Five speakers reflected on the connection between the minute research of the historian of ancient monuments, restoration practice and the policy for preservation. Prof. dr. ir. R. Meischke, chairman of that day, seriously wondered if this connection existed.The symposium perfectly made clear the distance between the desired and the actual connection of the research of historic buildings and the restoration practice. Many causes can be adduced. These causes were analyzed and most of the speakers, very often historians of ancient monuments themselves, did not hesitate to dive into their own hearts. One clearly was directed to the future.The world of the preservation of ancient monuments is in motion. Also the previously somewhat closed world of the historians of these monuments is changing. Researchers see themselves confronted with new problems of research. Conclusions from the past open perspectives and ways for the future.History of architecture is no stranger in the columns of this Bulletin. Regularly articles are published, which are based on the thorough research of ancient monuments. The reader however can seldom look behind the scenes. Which is presented in an agreeable way often has been fought under very difficult circumstances. History of architecture thereby constantly proved its value to both restoration practice and the improvement of the knowledge of ancient monuments. Therefore the editors of this Bulletin decided to publish the contents of this lectures, which have been slightly worked up by the speakers for publication.The lecture of Dr. L. de Vliegher, who revealed his ideas and experiences in his very own way did not lend itself for publication. Therefore this lecture has not been published. A short retrospective view on the course of the day is justified in this introduction. The occasion of this meeting was the farewell of Dr. H. Janse of the Ancient Monuments Department of the Ministry of Works because of his pensionable age. With this symposium the Ancient Monuments Department of the Ministry of Works dwelled on the research of historic buildings which has been given such an important impulse by Herman Janse and some honoured contemporaries and predecessors.The organization has been teased somewhat by sudden diseases of speakers. Mrs. Laleman and Mr. de Vries were very well replaced by Mr. Raveschot and Mr. de Jong. The cooperation of Belgian colleagues has been consciously sought after to enlarge the connection by exchange of experiences. This day also was seized upon to present two new appearances: the book Work and mark of the stonemason, the trade of the stonemason in the Netherlands before 1800 by H. Janse and D.J. de Vries and the announcement of the establishment of the foundation History of Ancient Monuments of the Netherlands. This foundation can be an underscore of the stage of maturity this discipline has reached in the Netherlands.